Human Capital Development, Remittances, and Poverty in Central and Eastern European Countries: What Do the Data Tell Us? - Tsaurai, Kunofiwa (Comparative Economic Research. Central and Eastern Europe, 2022)
The study investigates the impact of human capital development on poverty in Central and Eastern European Countries (CEECs) using dynamic generalized methods of moments (GMM), fixed effects, random effects, and pooled ordinary least squares (OLS) with panel data ranging from 2008 to 2019. Using the same panel data analysis methods and data set, the study also explored the influence of the complementarity between human capital development and personal remittances on poverty in CEECs. What triggered the investigation into this topic is that the available literature on the subject matter is mixed, divergent, and very much conflicting. The lag of poverty, remittances, the interaction between human capital development and remittances, trade openness, unemployment, and partly financial development significantly increased infant mortality rates in CEECs. On the other hand, human capital development, infrastructural development, and partly financial development were found to have reduced infant mortality rates. These results mean that human capital development, financial development, and infrastructural development reduced poverty in CEECs during the period under study. Central and Eastern European Countries are therefore urged to craft and implement financial development, infrastructural development, and human capital development enhancement policies to combat poverty. Future empirical research could also investigate at what threshold the level of human capital development, financial and infrastructural development would poverty be significantly reduced in CEECs.